Consequences of FTA Withdrawal: Evidence from "Uxit" - Hinnerk Gnutzmann; Arevik Gnutzmann-Mkrtchyan; Tobias Korn (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We use a unique case study to estimate the effect of withdrawing from a free trade agreement on international trade. Lately, the political opposition to international economic cooperation has been on the rise, but little is known about how the withdrawal from a trade agreement affects trade. We analyze a quasi-natural experiment to provide first empirical evidence. In 2004, Estonia joined the European Union, which mandated that it withdraws from its FTA with Ukraine (“Uxit”). Based on the gravity model of international trade, we provide evidence from triple difference–in–differences as well as PPML panel estimations that trade volumes between Estonia and Ukraine fell by more than 20%. We find that withdrawing an FTA revokes all benefits and that no institutional memory is left behind. General equilibrium estimates suggest that FTA withdrawal led to a noticeable loss in welfare of members.
Keywords: F13; F14; F15; F17; 330; free trade agreement; withdrawal; gravity; European Union; Estonia; Ukraine